ERRORS IN THE USE OF DICTION IN SCIENTIFIC ARTICLES: A CASE STUDY ON THE JOURNAL ALINEA VOL. 3 NO. 1 YEAR 2023 - Sandra, Novia Dwi; Yulianti, Upit; Putri, Febrina Riska (Bhandar: Harvesting Community Service in Asia, 2025)
The research aims to describe errors in using diction in student scientific articles: Case studies in Alinea Journal Vol. 3 No. 1 of 2023. This type of research is qualitative research. The method used in this research is descriptive method. The data in this research are words related to diction contained in scientific articles in the Alinea Journal Vol. 3 No.1 of 2023. The data source for this research is scientific articles in the Alinea Journal Vol. 3 No.1 of 2023. The data collection technique used in this research is listening and taking notes. The data validation technique in this research is the triangulation technique. Two methods can be used in the data analysis stage: the matching method and the agih method. The results of this research are diction errors contained in scientific articles in Alinea Journal Vol.3 No. 1 of 2023: a) errors in the use of denotative and connotative meaning diction, b) errors in the use of synonymous words diction.